Detailed structure of microlayer in nucleate pool boiling for water measured by laser interferometric method. (May 2017) - Chen, Zhihao; Haginiwa, Atsushi; Utaka, Yoshio
Highlights: The microlayer thickness distribution for water is measured by laser interferometric method. Two structure of microlayer at different stage in a bubble cycle is confirmed. The observation of bended shape of initial microlayer is shown in later stage of bubble cycle. The bended shape of microlayer has a close relation to the behavior of bubble detachment. Abstract: During nucleate pooling boiling, a microlayer forms on the heat transfer surface beneath a growing bubble. In previous studies, the existence of a microlayer was confirmed, and its structure was investigated by using several different experimental methods. However, the characteristics and mechanism of the formation of a microlayer have not been thoroughly elucidated to date. In this study, in order to obtain further understanding on the microlayer structure, a laser interferometric method was adopted for a more detailed observation. As a result, it was observed that the special bended shape of the microlayer forms near its outer margin when the microlayer radius is close to its maximum value. By analyzing the variation of the ratio of bubble height to diameter, it can be inferred that the detachment of a bubble causes a decrease of the initial microlayer thickness when the microlayer thickness is close to the maximum radius. This effect explains the formation of the bended shape of initial microlayer.